Dampak Psikososial Anak dan Remaja dengan Kanker dalam Reintegrasi Sekolah dan Sosial: Scoping Review - Ayu Kurniasih, Suci; Nurhidayah, Ikeu; Sumarni, Nina (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Cancer in children and adolescents is a global health challenge with increasing rates, making attention to quality of life during and after treatment increasingly important. Cancer treatment in children can have long-term effects on physical, cognitive, and psychosocial functioning that affect children’s participation in school and social environments. School and social reintegration are important aspects of the survivorship phase because they shape children’s identity, social relationships, and psychological well-being. Still, this process often faces challenges such as social stigma, isolation, and changes in peer relationships. This study aims to map the scientific evidence related to school and social reintegration in children and adolescents with cancer and its impact on psychological well-being. This study used a scoping review design with a PCC approach. Literature searches were conducted in international databases and selected according to PRISMA-ScR guidelines. A total of 12 articles met the inclusion criteria. The findings showed challenges in school reintegration, such as academic delays and concentration disorders. In the social aspect, stigma, isolation, changes in peer relationships, and bullying were the main obstacles. Psychological impacts included anxiety, decreased self-confidence, and quality of life, although some studies also showed resilience and positive growth. School and social reintegration in children and adolescents with cancer is a process that requires ongoing psychosocial support and cross-sector collaboration to improve psychological well-being.